Receiver psychology and the design of animal signals. - Guilford, T; Dawkins, MS (1993)
Animal communication is studied both by neurobiologists and by evolutionary biologists, but in very different ways. The purpose of this article is to show how both groups could benefit from a greater appreciation of each other's approach. Evolutionary biologists should take more account of the role played by the sensory systems and brains of receivers in constraining the design of animal signals. Neurobiologists should be more aware of recent advances in the understanding of signal-receiver co-evolution and the evolutionary origins of animal signals. A series of recent examples are cited that illustrate how pre-existing neurophysiological or psychological properties of receiver organisms are essential to our understanding of the design characteristics of animal signals and of their origins. Also discussed are a number of other areas of signalling in which the study of 'receiver psychology' is likely to be fruitful.